Granny is a darling - Denton, Kady MacDonald (New York : Aladdin Books, 1990)
When Billy shares his room with Granny one night, he learns something to banish his bedtime fears ever after.
"First published by Walker Books, Ltd., London, England"--p. facing t.p.
Keywords: Bedtime -- Fiction; Grandmothers -- Fiction